2020
DOI: 10.1016/j.jaci.2019.09.029
|View full text |Cite
|
Sign up to set email alerts
|

IκBζ is a key player in the antipsoriatic effects of secukinumab

Abstract: Background: IkBz plays a key role in psoriasis by mediating IL-17A-driven effects, but the molecular mechanism by which IL-17A regulates IkBz expression is not clarified. Objective: We sought to explore the molecular transformation in patients with psoriasis during anti-IL-17A (secukinumab) treatment with a focus on IkBz. Methods: The study was an open-label, single-arm, single-center secukinumab treatment study that included 14 patients with plaque psoriasis. Skin biopsy specimens and blood samples were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 43 publications
(55 reference statements)
5
34
0
Order By: Relevance
“…Keratinocytes are increasingly thought to play a key role in initiating the development of psoriasis as well as in amplifying the psoriatic inflammation during maintenance of lesions 7,28,29 . Moreover, studies in human keratinocytes have shown that IκBζ (the protein encoded by NFKBIZ ) is a key transcriptional regulator of CCL20 , IL36G and IL23A gene expression, 10,30,31 three genes known to play a crucial role in the psoriasis pathogenesis 1,10,24 . Thus, it is possible that RGRN‐305 mediates its immunomodulatory effects in human keratinocytes by inhibiting the IL‐17A+TNFα‐induced IκBζ expression and subsequently the expression of CCL20 , IL36G and IL23A as well as other IκBζ‐regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocytes are increasingly thought to play a key role in initiating the development of psoriasis as well as in amplifying the psoriatic inflammation during maintenance of lesions 7,28,29 . Moreover, studies in human keratinocytes have shown that IκBζ (the protein encoded by NFKBIZ ) is a key transcriptional regulator of CCL20 , IL36G and IL23A gene expression, 10,30,31 three genes known to play a crucial role in the psoriasis pathogenesis 1,10,24 . Thus, it is possible that RGRN‐305 mediates its immunomodulatory effects in human keratinocytes by inhibiting the IL‐17A+TNFα‐induced IκBζ expression and subsequently the expression of CCL20 , IL36G and IL23A as well as other IκBζ‐regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is well-known as an autoimmune disease of the joints and skin with inappropriate T cell activation. The transcriptional activator IκBζ induced by IL-17A-treated epithelial cells plays a key role in mediating the orchestrates downstream inflammatory responses in immune-related conditions, psoriasis (Bambouskova et al, 2018 ; Bertelsen et al, 2020 ). DI pretreatment interfere with the production of IκBζ in a way of electrophilic stress mediated by ATF3, a key mediator of the Nrf2-independent way and downregulate IκBζ protein correlated genes in primary keratinocytes stimulated by IL-17A (Bambouskova et al, 2018 ).…”
Section: The Candidate Mechanisms Of Itaconatementioning
confidence: 99%
“… 57 IκBζ (encoded by NFKBIZ ) has been proposed to play a key role in mediating the effects of IL-17A and IL-17F. 59–61 …”
Section: Treatmentmentioning
confidence: 99%